2020
DOI: 10.1186/s12889-020-09158-7
|View full text |Cite
|
Sign up to set email alerts
|

From long-term sickness absence to disability retirement: diagnostic and occupational class differences within the working-age Finnish population

Abstract: Background: It is well documented that sickness absence is strongly associated with disability retirement. A longterm sickness absence (LTSA) in particular increases the risk of disability retirement, but little is known about the variation of this risk across diagnostic causes. Further, as occupational classes differ in their diagnostic profiles, it is likely that the role of diagnosis in the pathway from LTSA to disability retirement varies between occupational classes. We examined how LTSA of different diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
1
17
0
1
Order By: Relevance
“…Reducing sickness absence entails two steps: first, preventing the occurrence of absence episodes, and second, preventing the prolongation of episodes that have already started. Especially long sickness absence is a strong predictor of permanently leaving the work force through disability retirement [ 8 , 9 , 10 , 11 ]. Great savings on the direct and indirect costs of work disability could be achieved through maintaining work ability in the working-age population and preventing long sickness absences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reducing sickness absence entails two steps: first, preventing the occurrence of absence episodes, and second, preventing the prolongation of episodes that have already started. Especially long sickness absence is a strong predictor of permanently leaving the work force through disability retirement [ 8 , 9 , 10 , 11 ]. Great savings on the direct and indirect costs of work disability could be achieved through maintaining work ability in the working-age population and preventing long sickness absences.…”
Section: Discussionmentioning
confidence: 99%
“…The covariates included gender, age (used in age bands 25–34, 35–44, 45–54 and 55–62 years), marital status (married, never married including those with unknown marital status, and divorced or widowed) and region of residence (four large regions based on geographic location) at the end of 2012, and taxable yearly income during 2012 (including both earned income and capital income, classified into quintiles). These covariates were taken into account since various socio-demographic variables are important predictors of sickness absence and may also confound the association between occupational class and disability [ 10 , 11 , 12 , 13 , 14 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with a more recent Danish study, which found that back disorders, mental disorders, and cancer were the health problems predicting long-term sickness absences in a two-year register based follow-up of a general population sample [ 42 ]. Long sickness absences due to mental problems showed large differences by occupational class with any disability retirement among Finns in 2007–2014 [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This generally higher attendance rate may be reflected in the higher proportion of FAs as well. Musculoskeletal disorders are both clearly more frequent [ 48 ] and pose a greater risk for disability retirement [ 49 ] among lower non-manual and manual employees than among upper non-manual employees. These disorders probably account for the higher FA rate in the OHS scheme as well.…”
Section: Discussionmentioning
confidence: 99%